A Cell-Based Approach to the Treatment of Inflammatory Bowel Disease—Entering an Era of Regenerative Medicine. Issue 8 (17th May 2018) - Lightner, Amy L
Abstract: Corticosteroids, and more recently biologics, have been the mainstay of therapy for patients with inflammatory bowel disease. Unfortunately, both are fraught with side effects and limited by lack of efficacy or loss of response. Many patients ultimately succumb to medically refractory disease and require an operation. As we enter an era of regenerative medicine, a new genre of cell-based therapeutics offers significant promise for both an improved safety profile and improved efficacy compared with conventional treatment approaches. The ability to restore and rebuild health with autologous products rather than react to disease with pharmaceuticals gives hope to those who treat inflammatory bowel disease. The rationale and ongoing trials in an emerging field of medicine—regenerative medicine—is herein discussed.